FORECAST STRUCTURE DEVELOPMENT FOR MODELLING THE SOUTHERN BRAZILIAN CONTINENTAL SHELF HYDRODYNAMIC - Stringari, C. E.; Kirinus, E. P.; Costi, J.; Oleinik, P. H.; Marques, W. C. (Revista de Engenharia Térmica, 2017)
Global forecast models have been widely used worldwide; however, they lack ability to prescribe high quality local data. In this paper, an assembly of oceanographic (RTOFS) and atmospheric (GFS) global data base are used to set up a nested forecast system. The approach proposed relies on the sage of python and FORTRAN scripts to download and assemble global metocean data, in addition to interpolate it towards the study area numerical grid as boundary conditions. Therefore, the TELEMAC-3D hydrodynamic model is automatically initiated in order to provide the regional forecast for the Southern Brazilian Continental Shelf. Results shows that the methodology proposed represent properly the flow dynamics inside the Patos Lagoon and also in the Tramandaí beach, with low/high frequency dynamic effects and influences being reported.